ANALISIS HUKUM TERHADAP OBJEK JAMINAN FIDUSIA MUSNAH KARENA HILANG APABILA OBJEK JAMINAN DITEMUKAN KEMBALI - Usril Usril (Jurnal Ilmu Hukum, 2018)
The purpose of this paper is to analyze the object of fiduciary collateral disappeared as lost if the object of the guarantee is rediscovered. Fiduciary Guaranty is the right of guarantee of tangible and intangible moving objects and movable objects which can not be burdened by mortgage as regulated in Law Number 4 Year 1996 concerning Deposit Rights which remain in the control of fiducia giver, as collateral for debt repayment which gives priority to the fiduciary recipient to the other creditor.